Badanie zależności między nadużywaniem substancji psychoaktywnych a funkcjami poznawczymi w populacji Ekwadoru - Vilchez, Jose Luis (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2017)
Aim of the study : The lack of studies on the cognitive consequences of psychotropic substance abuse makes it necessary to perform an in-depth analysis of its importance. Drug-rehabilitation centres in the Republic of Ecuador do not usually take into account neurocognitive stimulation within the treatments they offer. The aim of the present study is to test the effect of drug abuse in three different cognitive processes (learning, memory, and cognitive flexibility). Material and methods : To this aim, a version of the Wisconsin test was computerised to evaluate reaction times in diagnosed/consumer and undiagnosed/non-consumer populations. Results : The results show that diagnosed/consumer population has significantly greater reaction times in the matching tasks than the undiagnosed/non-consumer population; showing more important cognitive deficits in the cognitive areas of learning, memory and cognitive flexibility. On the other hand, there is a positive and significant correlation between time of consumption and the level of cognitive deficit. However, undiagnosed/non-consumer population significantly commit less number of mistakes in those tasks. Conclusions : It is recommended that drug-rehabilitation centres include cognitive rehabilitation in their intervention programming.